Primary catastrophic antiphospholipid syndrome in children with midbrain infarction: a case report - Dong, Qinghua; Yin, Jianyun; Su, Hang; Ni, Qian (Frontiers in Pediatrics, 2024)
Background Catastrophic antiphospholipid syndrome (CAPS) is a multi-system autoimmune disease characterized by extensive thrombosis. Pediatric CAPS is extremely rare and associated with a high mortality rate, especially when midbrain infarction is involved. Hence, early diagnosis and prompt initiation of appropriate treatment for CAPS complicated by midbrain infarction are of utmost importance in achieving favorable outcomes. Case presentation In this report, we present the case of a 14-year-old girl who presented with neurological symptoms and digestive system infection and was initially diagnosed with an “intracranial infection”. After a series of rigorous diagnostic procedures, the patient was ultimately diagnosed with primary CAPS and was immediately transferred to the intensive care unit where she was treated with anticoagulation, glucocorticoids, intravenous immunoglobulin (IVIG) therapy, and multiple plasma infusions. Twenty-seven days after admission, the patient's condition improved with standardized treatment, and she was discharged and followed up regularly. Conclusion This case report provides a description of the clinical features observed in a pediatric patient with CAPS and concurrent midbrain infarction, highlighting the crucial role of early diagnosis and timely treatment in influencing patient prognosis.